PENGARUH KONTROL DIRI, LITERASI EKONOMI DAN PROMOSI PENJUALAN TERHADAP PERILAKU PEMBELIAN IMPULSIF(Pengguna Shopee di DKI Jakarta) - Masayu Annisa Nuraini Tirta, (2022)
Shopee is an e-commerce which according to consumers the application is easy to use. Because of the convenience and comfort provided, of course consumers are interested and continue to shop online at Shopee. This research is a quantitative study that aims to determine the effect of self-control, economic literacy and sales promotion on impulsive buying behavior among Shopee users in DKI Jakarta. The sampling technique used in this study is non-probability sampling using purposive sampling method. The data collection carried out in this study was using a questionnaire and distributing it online with Googleform, then distributing it through various social media such as line, whatsapp, instastory and telegram groups. This research uses SmartPLS 3.2.9 software. And this study got the results, the self-control variabel has a negative effect on impulsive buying behavior. Then the economic literacy variabel has a positive effect on impulsive buying behavior, and the sales promotion variabel has a positive effect on impulsive buying behavior.